2003
DOI: 10.1002/j.1556-6678.2003.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Ego Identity Status: A Step in the Differentiation Process

Abstract: This study examined the relationship between identity development and differentiation levels in young adults. A total of 259 participants completed the Extended Version of the Objective Measure of Ego Identity Status (H. D. Grotevant & G. R. Adams, 1984), the Differentiation of Self Inventory (E. A. Skowron & M. L. Friedlander, 1998), and demographic questions. Results showed that each identity status had a unique effect on the various components of differentiation. Implications of the results for counselors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…In regard to emotional reactivity, the results were as expected and support previous findings related to the importance of reactivity in the identity and differentiation process (Johnson & Buboltz, 2000;Johnson et al, 2003). Specifically, results suggest that individuals who respond to environmental stimuli with emotional flooding, emotional lability, or hypersensitivity (i.e., reactivity) are less confident in their abilities (i.e., autonomy versus shame and doubt) and have a less stable identity (i.e., identity versus identity confusion).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In regard to emotional reactivity, the results were as expected and support previous findings related to the importance of reactivity in the identity and differentiation process (Johnson & Buboltz, 2000;Johnson et al, 2003). Specifically, results suggest that individuals who respond to environmental stimuli with emotional flooding, emotional lability, or hypersensitivity (i.e., reactivity) are less confident in their abilities (i.e., autonomy versus shame and doubt) and have a less stable identity (i.e., identity versus identity confusion).…”
Section: Discussionsupporting
confidence: 91%
“…Another dimension of psychological adjustment that has been theoretically (Bray & Harvey, 1992;Carter & McGoldrick, 1999) and empirically (Johnson, Buboltz, & Seemann, 2003) linked to differentiation is identity development. However, the relationship between differentiation and a more comprehensive understanding of psychosocial development needs to be explored.…”
mentioning
confidence: 98%
“…This study supported what Johnson et al (2003) found, in that identity status is related to differentiation. Therefore, it would behoove future researchers to determine whether or not doing transgenerational therapy with a father will help a therapist to work with a client in achieving identity to increase differentiation among fathers.…”
Section: Discussionsupporting
confidence: 94%
“…These individuals may be experiencing a similar level of turbulence in the career development process. This turbulence associated with moratorium, which has been shown to be related to reactivity and cutoff (Johnson et al, ), may be what is accounting for the lack of vocational identity and lower levels of decisiveness. Thus, it would make sense that as in the case of moratorium, individuals from our study who scored high on levels of emotional cutoff and reactivity are searching, but not yet able to make clear career decisions and develop a stable vocational identity.…”
Section: Discussionmentioning
confidence: 99%